Implementing Experiential Learning on Students Reading Comprehension - Hamid Ismail; Saiful Saiful (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The goal of this study is to expand on the use of experiential learning in students' reading comprehension. The method used in this study is called a "pre experiment." Pre-test, treatment, and post-test are all included in it. The purpose of the initial pretest was to learn more about the audience before they read. Treatment is the implementation of the experiential learning theory in the learning to learn program, which is done roughly three times. The purpose of the final posttest is to understand how students learn after being instructed using the experiential learning theory. Matriculants in the second semester of the STKIP Kie Raha Ternate English language program for the academic year 2020–2021 make up the majority of this study. Population: 172 students. The research was applied purposive sampling technique. It is meant that the researchers choose one class which consists of 30 students. The result can be reported that the students’ achievement in reading in pretest was classified as poor (X1 = 5,3)  and the students’ achievement in reading posttest was classified as good score were (X2 = 7.83 ). For the level of significance (P) = 0,05 and degree of freedom (df) = N – 1 (29), then the value of t-table (25.3 > 2.045). It means that, there was significant difference between the pretest and posttest score of the students’ reading comprehension by Experiential learning theory. In other words, the Null hypothesis (HO) is rejected and the alternative hypothesis (H1) is accepted. From the analysis above, the researchers concluded that there was significance different between the score that got by students in pretest and posttest in learning reading comprehension by Experiential learning theory.